(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
“Wujuh wa nazair” –the Qurʼanic discipline that studies the multiple senses (wujuh) a single word may carry and the different words that share one meaning (nazair) –is among the oldest branches of the Qurʼanic sciences. This article traces the historical formation of the field and surveys the scholars who composed works in it from the era of the Companions onward. Particular attention is given to Muqatil ibn Sulayman al-Balkhi (d. 767), whose al-Wujuh wa-n-nazair fi-l-Qurʼan al-azim is recognized as the earliest complete surviving work in the field, as well as to the testimony of Ibn al-Jawzi and later bibliographers concerning earlier and subsequent authors whose works have not survived. The article also examines the critical assessments directed at Muqatil and argues that, given the conventional structure of wujuh-wa-nazair works, an authorʼs doctrinal affiliation could not materially affect their content.